Synthesis of new DPP-4 inhibitors based on a novel tricyclic scaffold - Schwehm, Carolin; Li, Jin; Song, Hongmei; Hu, Xiao; Kellam, Barrie; Stocks, Michael (American Chemical Society, 2015)
A novel molecular scaffold has been synthesized and its synthesis and incorporation into new analogues of biologically active molecules will be discussed. A comparison of the inhibitory activity of these compounds to the known type-2 diabetes compound (sitagliptin) against dipeptidyl peptidase-4 (DPP-4) will be shown.